Imatinib mesylate (Glivec) inhibits Schwann cell viability and reduces the size of human plexiform neurofibroma in a xenograft model - Demestre, Maria; Herzberg, Jan; Holtkamp, Nikola; Hagel, Christian; Reuss, David; Friedrich, Reinhard E.; Kluwe, Lan; Deimling, Andreas von; Mautner, Victor Felix; Kurtz, Andreas (Journal of neuro-oncology, 2010)
Plexiform neurofibromas (PNF), one of the major features of neurofibromatosis type 1 (NF1), are characterized by complex cellular composition and mostly slow but variable growth patterns. In this study, we examined the effect of imatinib mesylate, a receptor tyrosine kinase inhibitor, on PNF-derived Schwann cells and PNF tumour growth in vitro and in vivo. In vitro, PNF-derived primary Schwann cells express platelet-derived growth factors receptors (PDGFR) alpha and beta, both targets of imatinib, and cell viability was reduced by imatinib mesylate, with 50% inhibition concentration (IC(50)) of 10 microM. For in vivo studies, PNF tumour fragments xenografted onto the sciatic nerve of athymic nude mice were first characterized. The tumours persisted for at least 63 days and maintained typical characteristics of PNFs such as complex cellular composition, low proliferation rate and angiogenesis. A transient enlargement of the graft size was due to inflammation by host cells. Treatment with imatinib mesylate at a daily dose of 75 mg/kg for 4 weeks reduced the graft size by an average of 80% (n = 8), significantly different from the original sizes within the group and from sizes of the grafts in 11 untreated mice in the control group (P < 0.001). We demonstrated that grafting human PNF tumour fragments into nude mice provides an adequate in vivo model for drug testing. Our results provide in vivo and in vitro evidence for efficacy of imatinib mesylate for PNF.
Online veröffentlicht: 17 November 2009
Gesehen am 05.01.2024